Highly efficient, reversible iodine capture and exceptional uptake of amines in viologen-based porous organic polymers. Issue 35 (28th May 2020) - Li, Meiting; Zhao, Huanyu; Lu, Zhong-Yuan
Abstract : Viologen-based porous organic polymers as highly efficient and reversible adsorbents for iodine and amines. Abstract : A viologen-based porous organic polymer, POP-V-VI, was designed and synthesized by a facile nucleophilic substitution between cyanuric chloride and 1, 2-bis(4-pyridinium) ethylene. Together with the reported POP-V-BPY with a similar structure, these viologen-based porous organic polymers bear high charge density, phenyl ring and nitrogenous affinity sites, which endow them with excellent iodine vapor uptake capacity (4860 mg g −1 for POP-V-VI and 4200 mg g −1 for POP-V-BPY) and remarkably high adsorption capacity for pyridine (4470 mg g −1 for POP-V-VI and 8880 mg g −1 for POP-V-BPY) and other aliphatic amines. POP-V-VI and POP-V-BPY could be efficiently recycled and reused three times without significant loss of iodine vapor uptake. All these results demonstrate that POP-V-VI and POP-V-BPY are promising adsorbents for practical applications in portable devices such as gas masks.